rhACE2 Therapy Modifies Bleomycin-Induced Pulmonary Hypertension via Rescue of Vascular Remodeling - Rathinasabapathy, Anandharajan; Bryant, Andrew J.; Suzuki, Toshio; Moore, Christy; Shay, Sheila; Gladson, Santhi; West, James D.; Carrier, Erica J. (Frontiers in Physiology, 2018)
Background: Pulmonary hypertension (PH) is a progressive cardiovascular disease, characterized by endothelial and smooth muscle dysfunction and vascular remodeling, followed by right heart failure. Group III PH develops secondarily to chronic lung disease such as idiopathic pulmonary fibrosis (IPF), and both hastens and predicts mortality despite of all known pharmacological interventions. Thus, there is urgent need for development of newer treatment strategies. Objective: Angiotensin converting enzyme 2 (ACE2), a member of the renin angiotensin family, is therapeutically beneficial in animal models of pulmonary vascular diseases and is currently in human clinical trials for primary PH. Although previous studies suggest that administration of ACE2 prevents PH secondary to bleomycin-induced murine IPF, it is unknown whether ACE2 can reverse or treat existing disease. Therefore, in the present study, we tested the efficacy of ACE2 in arresting the progression of group 3 PH. Methods: To establish pulmonary fibrosis, we administered 0.018 U/g bleomycin 2x/week for 4 weeks in adult FVB/N mice, and sacrificed 5 weeks following the first injection. ACE2 or vehicle was administered via osmotic pump for the final 2 weeks, beginning 3 weeks after bleomycin. Echocardiography and hemodynamic assessment was performed prior to sacrifice and tissue collection. Results: Administration of bleomycin significantly increased lung collagen expression, pulmonary vascular remodeling, and pulmonary arterial pressure, and led to mild right ventricular hypertrophy. Acute treatment with ACE2 significantly attenuated vascular remodeling and increased pulmonary SOD2 expression without measurable effects on pulmonary fibrosis. This was associated with nonsignificant positive effects on pulmonary arterial pressure and cardiac function. Conclusion: Collectively, our findings enumerate that ACE2 treatment improved pulmonary vascular muscularization following bleomycin exposure, concomitant with increased SOD2 expression. Although it may not alter the pulmonary disease course of IPF, ACE2 could be an effective therapeutic strategy for the treatment of group 3 PH.